Housing Deficit Index (HDI) in Brazil: analysis based on the 2022 Census Data - Polidoro, Maurício; Oliveira, Daniel Canavese de (Sustainability in Debate, 2025)
This study analyses the Housing Deficit Index (HDI) in Brazil based on data from the 2022 Demographic Census. The index incorporates indicators of inadequate access to water supply, sanitation, and solid waste management. A cross-sectional ecological design was applied, using descriptive statistics, Pearson and Spearman correlation coefficients, and the Kruskal-Wallis test. Results show significant regional and urban-rural disparities, with the worst housing conditions concentrated in the North and Northeast regions. The HDI was strongly correlated with the Municipal Human Development Index (MHDI) and moderately associated with the Brazilian Deprivation Index (IBP). In addition, municipalities classified as more deprived exhibited significantly higher proportions of non-white populations, reinforcing the relationship between housing precariousness and structural racial inequality. The HDI proved to be a robust and replicable tool for monitoring housing deprivation, offering support for territorialised public policies aimed at reducing socio-spatial and racial disparities in access to basic infrastructure.